Chronic Exposure to High Concentrations of Road Salt Decreases the Immune Response of Dragonfly Larvae - Mangahas, Racquelle S.; Murray, Rosalind L.; McCauley, Shannon J. (Frontiers in Ecology and Evolution, 2019)
Salinization of freshwater ecosystems, due to the application of road salts, is recognized as a potential threat to aquatic communities. Much of the research on the impact of salinity has focused on performance metrics in vertebrates, including respiration and osmoregulation. Here we focus on immune function in of the dragonfly Anax junius, a top predator in fishless aquatic habitats. Impacts on this top predator have the potential to cascade through the community, and immune function is known to be both plastic and sensitive to stress. We injected larvae with monofilaments (simulating a parasite) and placed them in one of three environmentally relevant concentrations of deicing road salt: control (dechlorinated tap water with no added salt), low (1000 mgL-1), or high salt (3000 mgL-1), for either acute (24hr) chronic or (96hr) exposures. We hypothesized that elevated salinity would suppress the immune response and that longer exposure magnifies this effect. As predicted, chronic exposure to high salt concentrations resulted in a significantly reduced larval immune response, however, there was no detectable treatment effects in larvae exposed to low concentrations of road salt or to acute high concentrations. Our results demonstrate that prolonged exposure to high levels of road salt can compromise the immune response of dragonfly larvae. Our findings suggest that insects in aquatic environments that experience sustained environmental salt pollution will be more susceptible to parasites and pathogens, which in turn may affect the impact of this major predator on aquatic community dynamics.